Forced off the farm? Farmers' labor allocation response to land requisition in China. (August 2020) - Ma, Shuang; Mu, Ren
Highlights: Land requisition decisions made by administrative bureaucracies are independent of the observed household and individual characteristics. Land loss due to government requisition increases individual migration propensity by 4.5 to 6.8 percentage points. Land requisition has no impact on local off-farm engagement. Abstract: Land requisition has been an important way for local Chinese governments to generate revenue and promote urbanization, but little is known how the land-losing farmers cope. This study investigates the impact of land requisition on farmers' off-farm labor participation. We provide evidence that rural-urban migration is one way that land-losing farmers now adapt to land requisition. Using data from the China Household Finance Survey, we first show that village characteristics, not household characteristics, are the key determining factors for how likely a household is to lose land. With a traditional difference-in-differences (DD) model and a DD model with individual fixed effects, we show that land loss due to government requisition has a significant migration effect in the total sample: it increases individual migration rates by 4.5–6.8 percentage points. Land requisition has no impact on local off-farm engagement. These findings are robust to using different samples, to correction for sample attrition, and to a falsification test. We also find that the migration effect is experienced in particular by younger and older farmers, by women, and by the better educated. From a policy perspective, the labor allocation response to land requisition identified in this paper suggests that providing job training and social protection to land-losing farmers, and facilitating their migration to cities, could help them to cope with the experience of land loss.